Gadolinium‐based contrast agent exposures and physical and cognitive disability in multiple sclerosis. Issue 1 (1st October 2022) - Nakamura, Kunio; McGinley, Marisa P.; Jones, Stephen E.; Lowe, Mark J.; Cohen, Jeffrey A.; Ruggieri, Paul M.; Ontaneda, Daniel
Abstract: Background and Purpose: The clinical correlation of gadolinium‐based contrast agents (GBCAs) has not been well studied in multiple sclerosis (MS). We investigated the extent to which the number of GBCA administrations relates to self‐reported disability and performance measures. Methods: A cohort of MS patients was analyzed in this retrospective observational study. The main outcome was the association between the cumulative number of GBCA exposures (linear or macrocyclic GBCA), Patient‐Determined Disease Steps (PDDS), and measures of physical and cognitive performance (walking speed test, manual dexterity test [MDT], and processing speed test [PST]). The analysis was performed first cross‐sectionally and then longitudinally. Results: The cross‐sectional data included 1059 MS patients with a mean age of 44.0 years (standard deviation = 11.2). While the contrast ratio in globus pallidus weakly correlated with PDDS, MDT, and PST in a univariate correlational analysis (coefficients, 95% confidence interval [CI] = 0.11 [0.04, 0.18], 0.15 [0.08, 0.21], and –0.16 [–0.10, –0.23], respectively), the associations disappeared after covariate adjustment. A significant association was found between number of linear GBCA administrations and PDDS (coefficient [CI] = –0.131 [–0.196, –0.067]), and MDT associated with macrocyclic GBCA administrations (–0.385 [–0.616, –0.154]), but their signs indicated better outcomes in patients with greater GBCA exposures. The longitudinal data showed no significant detrimental effect of macrocyclic GBCA exposures. Conclusion: No detrimental effects were observed between GBCA exposure and self‐reported disability and standardized objective measures of physical and cognitive performance. While several weak associations were found, they indicated benefit on these measures.